Some considerations from psychology about postpartum depression: an integrative review (Research, Society and Development, 2022)
Postpartum depression is a term used to describe depressive disorders that appear in mothers after the birth of a child until the first year of life. It starts from the fourth to the eighth trimester of pregnancy, intensifies in the first six months after birth and lasts until the first year of life. Among the factors that contribute to the development of postpartum depression (PPD) are mothers with low education who live alone and without a partner to support them, multiparous mothers who have already consumed alcohol and/or cigarettes, who have already been exposed to a crisis of extreme stress or who already have a family history of depression. In this sense, the objective of this study is to report on the role of the psychologist through an integrative literature review. Thus, postpartum depression is a serious health problem due to its high prevalence, although it is usually mild, it is important to detect and treat it early so as not to harm the pregnant woman and the child. Regarding the articles found, it can be confirmed that most of them are based on diagnostic tools for depression and mood symptoms. The articles also show risk factors for the development of postpartum depression, such as multiple births, previous depression, lack of planning, etc. The role of the psychologist in the treatment of postpartum depression is very important. Among the approaches that the specialist now uses, cognitive-behavioral therapy stands out.